(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Learning English as a second language at preschools has been being implemented for a few years in Uzbekistan. Since that so many methods have been experienced in order to get success in teaching. Teaching children at the age of 5-6 should be sociable and unusual. It requires creativity and tools that interest children. However, some teachers complain of not getting concentration of children at preschool even though the room is equipped with everything needs. So only authentic materials is not enough to teach children suitibly. This article reveals effective ways of teaching and teaching strategies.